2002
DOI: 10.1128/jvi.76.6.2683-2691.2002
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of the Cytoplasmic Domain Induces Exposure of Conserved Regions in the Ectodomain of Human Immunodeficiency Virus Type 1 Envelope Protein

Abstract: We have described a CD4-independent variant of HXBc2, termed 8x, that binds directly to CXCR4 and mediates CD4-independent virus infection. Determinants for CD4 independence map to residues in the V3 and V4-C4 domains together with a single nucleotide deletion in the transmembrane domain which introduces a frameshift (FS) at position 706. This FS results in a truncated cytoplasmic domain of 27 amino acids. We demonstrate here that while introduction of the 8x FS mutation into heterologous R5, X4, or R5X4 Env p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
177
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(189 citation statements)
references
References 67 publications
12
177
0
Order By: Relevance
“…During the circulation of the virus, the length of the tail has been correlated to a differential exposure of the virus to neutralizing antibodies (41). At the stage of entry, the cytoplasmic tail has also been implicated in regulating the kinetics of fusion and in the ability of the Env to promote syncytia (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…During the circulation of the virus, the length of the tail has been correlated to a differential exposure of the virus to neutralizing antibodies (41). At the stage of entry, the cytoplasmic tail has also been implicated in regulating the kinetics of fusion and in the ability of the Env to promote syncytia (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these domains may possibly interact with biological membranes, taking part in fusion reactivity (6, 16, 36 -40). (iii) Accumulated data indicate that gp41 CT LLP regions, which can interact with phospholipid membranes, may be involved in modulating cell-cell fusion by certain as-yet-undefined pathways (10,15,(17)(18)(19)(20)(21). It has been widely recognized that Gag matrix proteins mediate a mechanism of inside-out regulation of HIV-1 Env fusogenicity (18,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the gp41 CTs of HIV and simian immunodeficiency virus correlate with their infectivity and Env-mediated cell-cell fusion (10,15). The mutations or truncations of gp41 CT can affect HIV-1 Env-mediated cell-cell fusion, presumably because of modulation of the fusogenicity of Env (17,18). Kalia et al (15) discovered that one Env having a mutation in the gp41 CT LLP2 region (MX2) exhibited a decrease of about 90% in fusogenicity compared with the wildtype Env and that the mutation did not correspond to apparent defects in the levels of cell surface Env expression.…”
mentioning
confidence: 99%
“…Many examples in the literature describe the cytoplasmic domain as important for the function of the ectodomains of glycoproteins in a variety of virus families [16][17][18][19][20]. Studies examining conformation dependent binding of monoclonal antibodies showed that alterations in the cytoplasmic domain led to structural changes in the ectodomain [21,22]. Moreover, our data highlight that the cytoplasmic domain is an important factor for a correct quaternary structure, which subsequently is required for proper proteolytic processing and function of the viral glycoprotein.…”
Section: The Cytoplasmic Domain Stabilizes Non-cleaved Gp-c For Maturmentioning
confidence: 99%